Prenatal methamphetamine exposure causes dysfunction in glucose metabolism and low birthweight - Doi, Miyuki; Nakama, Nanako; Sumi, Takuya; Usui, Noriyoshi; Shimada, Shoichi (Frontiers in Endocrinology, 2022)
Methamphetamine (METH) is a psychostimulant drug that induces addiction. Previous epidemiological studies have demonstrated that maternal METH abuse during pregnancy causes low birthweight (LBW) in the offspring. As a source of essential nutrients, in particular glucose, the placenta plays a key role in fetal development. LBW leads to health problems such as obesity, diabetes, and neurodevelopmental disorders (NDDs). However, the detailed mechanism underlying offspring’s LBW and health hazards caused by METH are not fully understood. Therefore, we investigated the effects of prenatal METH exposure on LBW and fetal-placental relationship by focusing on metabolism. We found dysfunction of insulin production in the pancreas of fetuses exposed to METH. We also found a reduction of the glycogen cells (GCs) storing glycogens in the junctional zone of placenta, all of which suggest abnormal glucose metabolism affects the fetal development. These results suggest that dysfunction in fetal glucose metabolism may cause LBW and future health hazards. Our findings provide novel insights into the cause of LBW via the fetal-placental crosstalk.